Revisión de literatura de la pedagogía aplicada en la cátedra de la paz en Colombia para el período 2019-2024 (2024)
This compilation monograph investigates the way in which different sources and authors conceptualize, execute and reflect on the peace class as a tool for education, teaching and transformation in different areas and contexts framed in the armed conflict and post-agreement with the FARC. EP. This in order to find good practice processes, significant experiences and possibilities for improvement or application in other contexts. All with the objective of promoting peace education, the culture of non-violence, forgiveness, historical memory and the repair of the social fabric.